Pengaruh Latihan Beban Overhead Extension terhadap Kemampuan Lemparan Jarak Jauh dalam Permainan Sepakbola - Apriyanti, Habibah; Safari, Indra; Ahmad Fauzi, Rizal (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to determine the effect of overhead extension weight training on long-distance throwing ability in football games. This research uses a quantitative method with a pre-experimental approach. It uses a One Group Pre-test Post-test Design research design to determine the differences before and after being given specific treatment. The population in this study were SSB Ranc FC KU-10-year students, with a sample of 20 people. Data collection techniques use tests and measurements, while data analysis is carried out using descriptive analysis techniques. They are using the throwing test as an instrument in research. This study found that the average score on the final throwing test was higher than the initial test. The conclusion shows that overhead extension weight training can improve the ability to throw long distances in football games in SSB Ranc FC KU-10 year-students in RancakalongKeywords: Football, Throwing, Weight Training,